Credibility Of Electronic Word-Of-Mouth On Social Networking Sites And Its Impact On Brand Image And Purchase Intention: English - Pimpin Panohaj; Asmai Ishak (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to examine the influence of credibility Electronic Word of Mouth on social networking sites (SNS) and its impact on brand image and purchase intention. In this study, the population used is all people in Indonesia who have social media accounts. The number of samples is 210 respondents with age criteria of 16-46 years. The research data was obtained using a questionnaire via an online survey via google form. The data analysis technique uses Structural Equation Modeling (SEM) on the AMOS 26 program. The results of this study prove that the High Involvement has a positive effect on e-WOM, Trust has a positive effect on e-WOM, Recommendations have a positive effect on e-WOM, and Message Content has a positive effect on Electronic Word-of-Mouth (E-WOM), Electronic Word-of-Mouth has a positive effect on Brand Image, and Brand Image has a positive effect on Purchase Intention.